Language Revival or Language Construction? - Guillaume Enguehard (RiCognizioni, 2025)
The aim of this paper is to show that constructed languages provide rele- vant methods for the reconstruction and revitalization of natural languages. I use the example of Normannique, a reconstructed Scandinavian language de- rived from remnants of Old Norse found in Normandy’s place names (France) and currently the focus of a modest revitalization program. Since August 2024, this language has had a website with resources (normannique.org) and a youtube channel featuring 114 subscribers (youtube.com/@normannique). First, I address the difference between constructed and natural languages. I argue that the languages classified in these categories sometimes have the same degree of arbitrariness. It is therefore not so much the arbitrary aspect of language planning as the population’s attitude towards the language that defines its classification as a constructed or natural language. In a second step, I show that the arbitrary nature of language planning can lead to a po- sitive attitude among the population when it fulfils a function aimed in par- ticular at improving the feasibility of a revitalization process. Thus, despite being classified as natural, revived languages are not always distinguishable in practice from constructed languages. Finally, I show that conventional me- thods of linguistics, unlike the planning methods developed for constructed languages, struggle to take this feasibility criterion into account. I propose an example of a mixed method, which I illustrate using the Normannique language revival as an example.